Children of Vietnam - Lifton, Betty Jean; Fox, Thomas C. (New York : Atheneum, 1972)
Introduces several Vietnamese children with varying backgrounds: orphans, hippies, city and rural dwellers--all victims of war
Keywords: Vietnamese Conflict, 1961 -- 1975 -- Children -- Juvenile literature